Effect of organic and NPK fertilizers on flowering, pod formation, and seed production of cowpea (Vigna unguiculata L. Walp) - Fitratunnisah; Heni Purnamawati; Iskandar Lubis (Indonesia Society of Agronomy (PERAGI) and Department of Agronomy and Horticulture, Faculty of Agriculture, IPB University, Bogor, Indonesia, 2025)
Cowpea (Vigna unguiculata L. Walp), known as tolo beans in Indonesia, is a nutrient-dense legume consumed as young pods, dry seeds, or livestock feed. Despite its nutritional value and agronomic potential, cowpea productivity in Indonesia remains low. This study aimed to evaluate the effect of poultry manure and NPK fertilizers on flowering, pod formation, and seed filling of cowpea. The experiment was conducted from July to October 2024 at the Sawah Baru Experimental Field, IPB, using a randomized complete block design. Treatments included poultry manure at 0, 10, 20, and 30 tons ha-1 and NPK (16-16-16) at 0, 100, 200, and 300 kg ha-1. Results showed that poultry manure at 10-30 tons ha-1 and NPK above 100 kg ha-1 significantly increased the productive nodes at the ninth week after planting. Both fertilizers enhanced plant growth and yield. The highest average seed yield was obtained at 30 tons ha-1 poultry manure (3.64 tons grain ha-1) and 300 kg ha-1 NPK (3.38 tons grain ha-1), highlighting the benefit of integrating organic and inorganic fertilization to boost cowpea productivity. Keywords: cowpea; chicken manure; NPK fertilizer; kacang tolo